The Pivots of Global Energy and Geographical Location of Turkey - Akdemir, Ilhan Oguz; Kuscu, Veysel (Marmara Univ, 2012)
The world map is being refigured. The reason behind this turns around the new movement that is centered on the Middle East. We might state this reconfiguration process with reference to three main categories: 1-The demand for energy which is brought by increasing global population 2-The Security concerns on the Middle East and Middle Asian Countries which have increased in post 9/11 period. 3-The asymmetric war conducted by the USA and the NATO against the radical Islamist movement We can might different subjective analysis about these three broad categories. It is a common assumption that the energy transfer will change the national borders in the Middle East and influence Turkey. The main variable that will influence the future of Turkey is about the decision on the energy transfer pipelines that will transfer the energy between the Asian and the European countries. The pivot of the pipelines from the Caspian sea will be the key for the geopolitical importance of Turkey. Besides, the road that the African gas will follow is closely related with Turkey. Besides Turkey-Greece-Italy and Turkmenistan-Turkey-Europe gas pipeline projects, Egypt-Turkey, Iraq-Turkey and Nabucco pipeline projects will contribute to Turkey's importance and lead Turkey to benefit from its geographical position. The other alternatives, namely South Stream project, Trans-Asia projects, Iraq-Israel and Middle Asia-Pakistan projects are seen as projects that will diminish the importance of Turkey. The words of Pierre Noel, Professor of Cambridge University and EU Foreign Affairs researcher, show the importance of petropolitics on change: There is an open, competitive and capitalist economy in which firms are free to construct pipelines as they want. In case if the southern and northern Russia is decided as the path for the pipelines, the idea that Turkey will be more important actor in the geopolitical balance will be weakened. When we add the possibility of the transfer of African gas through the Mediterrenaian Sea and of Middle Eastern and Middle Asian petroleum and gas through countries other than Turkey, Turkey's geopolitical and geostrategic importance will decrease. In fact while assessing Turkey's diplomatic and geopolitical interests, one should consider the importance of the Afro-Eurasia centered energy transfer and the fact that the results cannot be taken only through diplomatic means. It is important to read the map through considering culture and politics rather than sole diplomatic lenses. Besides, while defining the energy politics of the country, it is important to consider the fact that petroleum and gas can be consumed in the long run. It should be understood that Turkey's future depends not on pratic geopolitics but on structural geopolitical processes.
Keywords: Turkey; Energy; Geography; Geopolitic; Petropolitic; Geographical Location